Method for producing electrostatic latent image developing toner

In the process of electrostatic latent image development, the aggregation of polyester resin particles and the adhesion of amorphous polyester resin particles, combined with heating and stirring control, the unstable charge amount and particle size of the toner for electrostatic latent image development are solved. Problem, stable and uniform development effect is achieved.

CN119225131APending Publication Date: 2024-12-31FUJIFILM BUSINESS INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410713627.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively manufacture the toner for electrostatic latent image development with a target charge amount, especially in the control of particle size and charge.

Method used

By aggregating in a dispersion containing polyester resin particles, the first aggregation particles are formed, and mixed with the dispersion of amorphous polyester resin particles, the amorphous polyester resin particles are adhered to the first by stirring The surface of the particles is aggregated to form a second agglomerated particle, and then the melting body is then satisfied by heating to satisfy specific temperature and stirring power conditions to control the particle size and charge.

Benefits of technology

A stable and uniform toner for electrostatic latent image development is achieved, and the particle size and charge amount can be controlled within the target range, thereby improving the development effect and product stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119225131A_ABST
    Figure CN119225131A_ABST
Patent Text Reader

Abstract

A method for producing an electrostatic latent image developing toner includes: a first aggregation step of aggregating polyester resin particles in a dispersion liquid containing the polyester resin particles to form first aggregated particles; a second aggregation step in which a dispersion containing the first aggregated particles and a dispersion containing amorphous polyester resin particles are mixed, and the amorphous polyester resin particles are adhered to the surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles; and a joining step of forming toner particles by heating the dispersion liquid containing the second aggregated particles to melt and join the second aggregated particles, the second aggregation step satisfying the following formulae (1), (2) and (3): (1) 35 < = Tc < = (Tgs-5), (2) 10 < = Ts < = Tc, and (3) 0.6 < = (P-P0) < = 3.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a toner for developing electrostatic latent images. Background Art

[0002] Patent document 1 discloses a method for producing a toner, which includes: a first agglomeration step of causing resin particles containing at least an amorphous polyester resin to at least agglomerate to produce a dispersion of a first toner particle precursor; a mixing step of mixing the dispersion of the first toner particle precursor and a dispersion of polyester resin particles having a carboxyl group to produce a dispersion of a second toner particle precursor; and a second agglomeration step of causing the second toner particle precursor to at least agglomerate to form toner particles.

[0003] Patent document 2 discloses a method for producing a toner for developing electrostatic latent images, which comprises: step (1) of mixing resin particles (A), release agent particles and a coagulant in an aqueous medium to obtain agglomerated particles (1), wherein the resin particles (A) contain a resin containing more than 90% by weight of a polyester resin (a), and the release agent particles contain wax and a polyester resin (b) having a softening point of 75 to 105°C in a weight ratio of 95 / 5 to 55 / 45; step (2) of mixing resin particles (B) containing a polyester resin (c) serving as a shell with the agglomerated particles (1) to obtain agglomerated particles (2); and step (3) of fusing the particles constituting the agglomerated particles (2) to obtain core-shell particles.

[0004] Patent Document 1: Japanese Patent Application Laid-Open No. 2010-145611

[0005] Patent Document 2: Japanese Patent Application Laid-Open No. 2012-128024 Summary of the Invention

[0006] An object of the present invention is to provide a method for producing a toner for developing electrostatic latent images, which can easily achieve a target charge amount.

[0007] Specific means for solving the above-mentioned problems include the following aspects.

[0008] <1>

[0009] A method for producing a toner for developing an electrostatic latent image, comprising:

[0010] a first aggregating step of aggregating the polyester resin particles in a dispersion containing the polyester resin particles to form first aggregated particles;

[0011] a second aggregation step of mixing a dispersion containing the first aggregated particles with a dispersion containing amorphous polyester resin particles, and causing the amorphous polyester resin particles to adhere to surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles; and

[0012] a fusion step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles to form toner particles;

[0013] The second coagulation step satisfies the following formulas (1), (2) and (3):

[0014] Formula (1): 35≤Tc≤(Tgs-5),

[0015] Formula (2): 10≤Ts≤Tc,

[0016] Formula (3): 0.6≤(P-P0)≤3.0,

[0017] Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles.

[0018] Tc is the temperature (°C) of the dispersion containing the first aggregated particles at the start of mixing,

[0019] Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing,

[0020] P is the stirring power per unit volume (kW / m 3 ),

[0021] P0 is the no-load stirring power per unit volume (kW / m 3 ).

[0022] <2>

[0023] The method for producing a toner for developing an electrostatic latent image according to <1>, wherein:

[0024] The acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less.

[0025] <3>

[0026] The method for producing a toner for developing an electrostatic latent image according to <1> or <2>, wherein:

[0027] The second aggregation step further satisfies the following equations (4) and (5):

[0028] Formula (4): 10≤Wc≤20,

[0029] Formula (5): 5≤(Ws-Wc)≤20,

[0030] Wc is the solid content concentration (mass %) of the dispersion containing the first aggregated particles at the start of mixing,

[0031] Ws is the solid content concentration (mass %) of the dispersion containing the amorphous polyester resin particles at the start of mixing.

[0032] <4>

[0033] The method for producing a toner for developing an electrostatic latent image according to any one of <1> to <3>, wherein

[0034] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion containing amorphous polyester resin particles and crystalline polyester resin particles.

[0035] The total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45% by mass or more of the total solid content of the dispersion containing the polyester resin particles.

[0036] <5>

[0037] The method for producing a toner for developing an electrostatic latent image according to any one of <1> to <4>, wherein

[0038] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing colorant particles.

[0039] The zeta potential of the colorant particle dispersion used to prepare the dispersion is -40 mV or more and -15 mV or less, measured with the solid content concentration, hydrogen ion concentration, and temperature of the colorant particle dispersion adjusted to 10% by mass, pH 6, and 25°C.

[0040] <6>

[0041] The method for producing a toner for developing an electrostatic latent image according to any one of <1> to <5>, wherein

[0042] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl resin particles.

[0043] The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 the following.

[0044] <7>

[0045] The method for producing a toner for developing an electrostatic latent image according to any one of <1> to <6>, wherein

[0046] In the second aggregation step, the dispersion containing the amorphous polyester resin particles further contains release agent particles.

[0047] <8>

[0048] The method for producing a toner for developing an electrostatic latent image according to any one of <1> to <7>, wherein

[0049] The first coagulation step, the second coagulation step, and the combining step are performed in a stirring tank equipped with a stirring member and a heating and cooling member.

[0050] Effects of the Invention

[0051] According to <1>, <7>, or <8>, a method for producing a toner for developing an electrostatic latent image that is more likely to achieve a target charge amount than when at least one of equations (1), (2), and (3) is not satisfied is provided.

[0052] According to <2>, a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is less than 8 mgKOH / g or exceeds 16 mgKOH / g.

[0053] According to <3>, a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when at least one of the equations (4) and (5) is not satisfied.

[0054] According to <4>, a method for producing a toner for developing electrostatic latent images is provided, which is more likely to achieve a target charge amount than when the total amount of amorphous polyester resin particles and crystalline polyester resin particles is less than 45% by mass of the total solid content of the dispersion in the first aggregation step.

[0055] According to <5>, a method for producing a toner for developing an electrostatic latent image is provided, which is capable of easily achieving a target charge amount compared to a case where the zeta potential of the colorant particle dispersion is less than -40 mV or exceeds -15 mV.

[0056] According to <6>, a method is provided in which the difference between the solubility parameter of the vinyl resin and the solubility parameter of the amorphous polyester resin exceeds 1.0 (cal / cm 3 ) 0.5 In the case of the above, it is easy to realize the method for producing a toner for developing an electrostatic latent image having a target charge amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Embodiments of the present invention will be described in detail with reference to the following drawings.

[0058] Figure 1 This is a schematic structural diagram showing an embodiment of a stirring tank used in the method for producing the toner for developing an electrostatic latent image according to the present embodiment.

[0059] Explanation of symbols

[0060] 10- stirring tank, 20- blade, 40- rotating shaft, 60- jacket, 80- baffle. DETAILED DESCRIPTION

[0061] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are provided to illustrate the embodiments and are not intended to limit the scope of the embodiments.

[0062] In the present invention, a numerical range expressed using “to” indicates a range including the numerical values ​​before and after “to” as the minimum value and the maximum value, respectively.

[0063] In the numerical ranges described in stages in the present invention, the upper limit or lower limit described in one numerical range may be replaced by the upper limit or lower limit of another numerical range described in stages. Furthermore, in the numerical ranges described in the present invention, the upper limit or lower limit of the numerical range may be replaced by the value shown in the Examples.

[0064] In the present invention, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0065] When the embodiments of the present invention are described with reference to the drawings, the structures of the embodiments are not limited to those shown in the drawings. Furthermore, the sizes of the components in the drawings are conceptual, and the relative sizes of the components are not limited thereto.

[0066] In the present invention, each component may contain multiple corresponding substances. When the amount of each component in the composition is mentioned in the present invention, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition.

[0067] In the present invention, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component represents a value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0068] In the present invention, “(meth)acrylic acid” includes both acrylic acid and methacrylic acid, and “(meth)acrylate” includes both acrylate and methacrylate.

[0069] In the present invention, “toner” means “toner for developing electrostatic latent images”, “developer” means “developer for developing electrostatic latent images”, and “carrier” means “carrier for developing electrostatic latent images”.

[0070] In the present invention, a method of producing toner particles by aggregating and combining material particles in a dispersion medium is referred to as an EA (Emulsion Aggregation) method.

[0071] <Method for producing toner for developing electrostatic latent images>

[0072] The toner production method according to this embodiment includes a step of producing toner particles by an EA method, and includes the following first aggregating step, second aggregating step, and combining step.

[0073] First aggregation step: a step of aggregating polyester resin particles in a dispersion containing polyester resin particles to form first aggregated particles.

[0074] Second aggregation step: a step of mixing a dispersion containing first aggregated particles and a dispersion containing amorphous polyester resin particles, and causing the amorphous polyester resin particles to adhere to the surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles.

[0075] Aggregation step: A step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles into a fusion body to form toner particles.

[0076] The first aggregation step forms the core of the core / shell toner particles. The second aggregation step forms the shell of the core / shell toner particles. Core / shell toner particles can be produced by going through the first and second aggregation steps and the combining step.

[0077] In the toner production method according to this embodiment, the second aggregation step satisfies the following formulas (1), (2), and (3).

[0078] Formula (1): 35≤Tc≤(Tgs-5)

[0079] Formula (2): 10≤Ts≤Tc

[0080] Formula (3): 0.6≤(P-P0)≤3.0

[0081] Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles.

[0082] Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing.

[0083] Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing.

[0084] P is the stirring power per unit volume (kW / m 3 ).

[0085] P0 is the no-load stirring power per unit volume (kW / m 3 ).

[0086] During the second coagulation step, the dispersion containing the first coagulated particles and the dispersion containing the amorphous polyester resin particles are stirred and mixed at a stirring power satisfying formula (3). The value of (P-P0) during the second coagulation step may be constant or variable as long as it is within the range of formula (3).

[0087] The value of (P-P0) is controlled by the viscosity and amount of the dispersion, the shape and size of the stirring member, and the rotation speed of the stirring member.

[0088] The value of P (kW / m 3 ) by using the volume of the dispersion in the second coagulation step (m 3 ) divided by the driving power (kW) of the stirring member operating in the second coagulation step. The volume of the dispersion in the second coagulation step gradually changes (in the early stages of the second coagulation step, it gradually increases due to mixing of the dispersion containing the first coagulated particles and the dispersion containing the amorphous polyester resin particles). This is the volume at each moment during the second coagulation step. The driving power of the stirring member is also the driving power at each moment during the second coagulation step.

[0089] The value of P0 (kW / m 3 ) is obtained by the following (1) and (2).

[0090] (1) Create an approximate formula that represents the relationship between the rotational speed (rpm) and the driving power (kW) of the stirring member used in the second coagulation step. The approximate formula is created based on the values ​​obtained by rotating the stirring member without a dispersion (referred to as "idling"), changing the rotational speed in four steps, and measuring the driving power at four points. The driving power is measured at one of the four points at the lowest possible rotational speed, and at the other point at the stirring member's rotational speed at the start of mixing in the second coagulation step. If idling of the stirring member is not recommended, the driving power is measured at the four points at the lowest possible rotational speeds in four steps.

[0091] (2) The rotation speed (rpm) of the stirring member in the second coagulation step is substituted into the approximate formula to calculate the driving power (kW), and the volume (m 3 ) divided by the calculated drive power to calculate the value of P0 (kW / m 3 The volume of the dispersion during the second coagulation step gradually changes (in the early stages of the second coagulation step, it gradually increases due to mixing of the dispersion containing the first coagulated particles and the dispersion containing the amorphous polyester resin particles). This volume is the volume at each point during the second coagulation step. The driving power of the stirring member is also the driving power at each point during the second coagulation step.

[0092] According to the toner manufacturing method of this embodiment, the particle size of the toner particles is controlled to a target value by satisfying equations (1), (2), and (3) in the second aggregation step. As a result, a toner can be manufactured that easily achieves a target charge amount in the developer. In the case of negative chargeability, the target charge amount of the developer is, in one example, not less than -90 μC / g and not more than -35 μC / g.

[0093] In the second aggregation step, as amorphous polyester resin particles adhere to the surfaces of the first aggregated particles, causing the second aggregated particles to grow, the particle size of the second aggregated particles fluctuates depending on the balance between the cohesive force between the particles and the shear force caused by stirring. It is speculated that by satisfying equations (1), (2), and (3) in the second aggregation step, the second aggregated particles grow stably, and the toner particles are more likely to grow to a target particle size range.

[0094] If Tc is less than 35°C, the cohesive force between particles is too low, and the shear force caused by stirring is excessive. This leads to insufficient adhesion of the amorphous polyester resin particles, small particle size growth, and a high proportion of fine particles. To suppress this, Tc is 35°C or higher, for example, preferably 38°C or higher, and more preferably 40°C or higher.

[0095] If Tc exceeds (Tgs-5), the cohesive force between particles becomes too high, and the shear force due to stirring becomes insufficient. As a result, the amorphous polyester resin particles adhere excessively, the particle size grows large, and the cohesive force becomes uneven, which tends to increase the proportion of coarse particles. To suppress this, Tc is (Tgs-5) or less, for example, preferably (Tgs-7) or less, and more preferably (Tgs-10) or less.

[0096] From the viewpoint of improving the heat storage properties of the toner, Tgs is, for example, preferably 50° C. or higher, more preferably 52° C. or higher, and even more preferably 54° C. or higher.

[0097] From the viewpoint of improving the low-temperature fixing ability of the toner, Tgs is, for example, preferably 70° C. or lower, more preferably 68° C. or lower, and even more preferably 65° C. or lower.

[0098] If Ts is less than 10°C, the temperature of the dispersion containing the first aggregated particles decreases locally, and the overall temperature of the system also decreases. This reduces the cohesive force between the particles, reduces particle size growth, and tends to increase the proportion of fine particles. To prevent this, Ts is 10°C or higher, for example, preferably 12°C or higher, and more preferably 15°C or higher.

[0099] If Ts exceeds Tc, the temperature of the dispersion containing the first agglomerated particles rises locally, and the overall temperature of the system also rises. As a result, the cohesive force between the particles becomes too high, the particle size grows large, and the cohesive force becomes uneven, which tends to increase the proportion of coarse particles. To suppress this, Ts is below Tc, for example, preferably below (Tc-10), more preferably below (Tc-20).

[0100] If (P-P0) is less than 0.6, the shear force due to stirring is insufficient, making it difficult to maintain a constant particle size growth despite disturbances such as resin properties and temperature. To suppress this, (P-P0) is 0.6 or greater, for example, preferably 0.8 or greater, and more preferably 1.0 or greater.

[0101] If (P-P0) exceeds 3.0, the shear force caused by stirring is excessive, so the proportion of fine particles becomes large, making it difficult to make the particle size growth constant. From the viewpoint of suppressing this situation, (P-P0) is 3.0 or less, for example, preferably 2.0 or less, more preferably 1.5 or less.

[0102] In the toner production method according to the present embodiment, for example, it is preferable that the second aggregation step further satisfies the following formulas (4) and (5).

[0103] Formula (4): 10≤Wc≤20

[0104] Formula (5): 5≤(Ws-Wc)≤20

[0105] Wc is the solid content concentration (mass %) of the dispersion containing the first aggregated particles at the start of mixing.

[0106] Ws is the solid content concentration (mass %) of the dispersion containing the amorphous polyester resin particles at the start of mixing.

[0107] From the viewpoint of improving the controllability of particle size and reducing the proportion of fine particles, Wc is, for example, preferably 10 mass % or more, more preferably 11 mass % or more, and even more preferably 12 mass % or more.

[0108] From the viewpoint of suppressing uneven mixing, Wc is, for example, preferably 20 mass % or less, more preferably 18 mass % or less, and further preferably 16 mass % or less.

[0109] From the viewpoint of increasing the cohesive force between particles and improving the adhesion of fine particles, (Ws-Wc) is, for example, preferably 5 mass % or more, more preferably 8 mass % or more, and even more preferably 10 mass % or more.

[0110] From the viewpoint of increasing the cohesive force between particles and uniformizing the particle size growth of the aggregated particles, (Ws-Wc) is, for example, preferably 20 mass % or less, more preferably 19 mass % or less, and even more preferably 18 mass % or less.

[0111] From the viewpoint of improving the adhesive force during shell formation, Ws is, for example, preferably 15 mass % or more, more preferably 20 mass % or more, and even more preferably 25 mass % or more.

[0112] From the viewpoint of improving the miscibility of the shell-forming dispersion (lowering the viscosity), Ws is, for example, preferably 45 mass % or less, more preferably 40 mass % or less, and even more preferably 35 mass % or less.

[0113] The first coagulation step, the second coagulation step, and the combining step are preferably performed in a stirring tank equipped with a stirring member and a heating and cooling member. The stirring member is preferably, for example, a stirring member having a rotating shaft and stirring blades. The heating and cooling member is preferably, for example, a member that applies and / or removes heat from the wall surface of the stirring tank.

[0114] Figure 1 It is a schematic structural diagram showing an embodiment example of a stirring tank.

[0115] Figure 1 The stirring tank 10 shown includes a blade 20 as an example of a stirring member and a jacket 60 as an example of a heating and cooling member.

[0116] The paddles 20 are provided in two stages on the rotating shaft 40. The rotating shaft 40 and the paddles 20 are rotated by a driving device (not shown), thereby stirring the dispersion contained in the stirring tank 10.

[0117] The jacket 60 has a flow path through which steam, water, or oil flows, and heats or cools the dispersion contained in the agitation tank 10 from the wall surface of the agitation tank 10 .

[0118] The agitation tank 10 may further include baffles 80. The baffles 80 are plate-shaped or cylindrical, and two, three, or four baffles 80 are provided at equal intervals on the inner side surface of the agitation tank 10.

[0119] Hereinafter, the steps and materials of the method for producing the toner according to this embodiment will be described in detail.

[0120] [First Coagulation Step]

[0121] The first aggregation step is a step of aggregating at least polyester resin particles in a dispersion containing at least polyester resin particles to form first aggregated particles.

[0122] Examples of the polyester resin particles include amorphous polyester resin particles and crystalline polyester resin particles. The polyester resin particles may be composed solely of amorphous polyester resin particles, crystalline polyester resin particles, or a combination of amorphous polyester resin particles and crystalline polyester resin particles.

[0123] Examples of the form of the dispersion subjected to the first aggregation step include a dispersion containing amorphous polyester resin particles and crystalline polyester resin particles, wherein the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles is 45% by mass or more of the total solid content of the dispersion.

[0124] When the total amount of the two polyester resin particles is 45% by mass or more of the total solids content of the dispersion, the amorphous polyester resin particles are more likely to adhere to the surfaces of the first aggregated particles in the second aggregation step. From this perspective, the total amount of the two polyester resin particles is, for example, more preferably 60% by mass or more of the total solids content of the dispersion, and even more preferably 75% by mass or more.

[0125] The total amount of the two polyester resin particles may be 100% by mass of the total solid content of the dispersion, or may be 95% by mass or less, or may be 85% by mass or less.

[0126] When the dispersion liquid provided to the first aggregation step contains amorphous polyester resin particles and crystalline polyester resin particles, the content ratio of the two polyester resin particles (amorphous polyester resin particles:crystalline polyester resin particles, mass ratio) is, for example, preferably 98:2 to 70:30, more preferably 95:5 to 75:25, and even more preferably 90:10 to 80:20.

[0127] The dispersion liquid provided to the first coagulation step may contain at least one of vinyl resin particles, release agent particles, and colorant particles. Therefore, the first coagulation step may be a step of coagulating at least one of the vinyl resin particles, release agent particles, and colorant particles together with the polyester resin particles.

[0128] The dispersions used in the first aggregation step can be prepared by, for example, separately preparing an amorphous polyester resin particle dispersion containing amorphous polyester resin particles, a crystalline polyester resin particle dispersion containing crystalline polyester resin particles, a vinyl resin particle dispersion containing vinyl resin particles, a release agent particle dispersion containing release agent particles, and a colorant particle dispersion containing colorant particles, and then mixing these particle dispersions. The order of mixing these particle dispersions is not limited.

[0129] Hereinafter, the amorphous polyester resin particle dispersion, crystalline polyester resin particle dispersion, vinyl resin particle dispersion, release agent particle dispersion, and colorant particle dispersion are collectively referred to as “particle dispersion” for their common features.

[0130] One example of an embodiment of the particle dispersion is a dispersion in which a material is dispersed in a dispersion medium in the form of particles by a surfactant.

[0131] The dispersion medium of the particle dispersion is preferably an aqueous medium. Examples of the aqueous medium include water and alcohol. Water, for example, is preferably water with reduced ion content, such as distilled water or deionized water. These aqueous media may be used alone or in combination of two or more.

[0132] The surfactant used to disperse the material in the dispersion medium can be any of anionic, cationic, and nonionic surfactants. Examples include anionic surfactants such as sulfate esters, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Surfactants can be used alone or in combination of two or more. Nonionic surfactants can be used in combination with anionic or cationic surfactants.

[0133] Examples of a method for dispersing the material in a dispersion medium in a particle form include known dispersion methods such as a rotary shearing homogenizer, a ball mill equipped with media, a sand mill, and a DYNO-MILL.

[0134] Phase inversion emulsification is a method for dispersing a resin in a dispersion medium in the form of particles. An example of a phase inversion emulsification method involves dissolving the resin in a hydrophobic organic solvent capable of dissolving the resin, adding a base to the organic continuous phase (phase O) for neutralization, and then adding an aqueous medium (phase W) to achieve a phase inversion from W / O to O / W, dispersing the resin in the form of particles in the aqueous medium.

[0135] The volume average particle size of the particles dispersed in the particle dispersion is, for example, preferably 30 nm to 300 nm, more preferably 50 nm to 250 nm, and even more preferably 80 nm to 200 nm.

[0136] The volume average particle size of particles in the particle dispersion refers to the particle size at which the cumulative total from the smaller diameter side reaches 50% in the particle size distribution measured using a laser diffraction particle size distribution analyzer (eg, LA-700 manufactured by HORIBA, Ltd.).

[0137] The content of the particles contained in each particle dispersion is, for example, preferably 5 mass % to 50 mass %, more preferably 10 mass % to 40 mass %, and even more preferably 15 mass % to 30 mass %.

[0138] Hereinafter, the materials constituting the particles of each of the amorphous polyester resin particle dispersion, the crystalline polyester resin particle dispersion, the vinyl resin particle dispersion, the release agent particle dispersion, and the colorant particle dispersion will be described.

[0139] -Amorphous polyester resin-

[0140] As the amorphous polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0141] Examples of the amorphous polyester resin include polycondensates of polycarboxylic acids and polyols.

[0142] Examples of the polycarboxylic acid as a polymerization component of the amorphous polyester resin include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, and sebacic acid), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid), and anhydrides or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.

[0143] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0144] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0145] Examples of the polyol as a polymerization component of the amorphous polyester resin include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-docosanediol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, as the polyol, for example, aliphatic diol is preferable.

[0146] As the polyol as the polymerization component of the amorphous polyester resin, a trivalent or higher valent polyol having a crosslinked or branched structure may be used together with a diol. Examples of the trivalent or higher valent polyol include glycerol, trimethylolpropane, and pentaerythritol.

[0147] The polyols may be used alone or in combination of two or more.

[0148] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 70° C. or lower, more preferably 52° C. or higher and 68° C. or lower, and further preferably 54° C. or higher and 65° C. or lower.

[0149] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition onset temperature" method described in JIS K7121-1987 "Plastics - Determination of Transition Temperatures".

[0150] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0151] The number average molecular weight (Mn) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.

[0152] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0153] The weight-average molecular weight and number-average molecular weight were measured by gel permeation chromatography (GPC). Molecular weight determination by GPC was performed using a GPC HLC-8120GPC manufactured by TOSOH CORPORATION as the measuring apparatus, a TSKgel SuperHM-M (15 cm) column manufactured by TOSOH CORPORATION was used, and THF was used as the solvent. The weight-average molecular weight and number-average molecular weight were calculated using a molecular weight calibration curve prepared from monodisperse polystyrene standard samples based on the measurement results.

[0154] Amorphous polyester resins are obtained by known production methods. Specifically, for example, they are obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as needed, and carrying out the reaction while removing water and alcohol generated during condensation.

[0155] If the raw monomers are insoluble or incompatible at the reaction temperature, a high-boiling-point solvent may be added as a cosolvent to dissolve them. In this case, the polycondensation reaction is carried out while the cosolvent is distilled off. If a monomer with poor compatibility is present during the copolymerization reaction, for example, the monomer with poor compatibility may be condensed with the acid or alcohol to be polycondensed with the monomer before polycondensation with the main component.

[0156] -Crystalline polyester resin-

[0157] As the crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0158] Examples of crystalline polyester resins include polycondensates of polycarboxylic acids and polyols. Since crystalline polyester resins easily form a crystalline structure, polycondensates of linear aliphatic polymerizable monomers are preferred over polycondensates of polymerizable monomers having an aromatic ring.

[0159] Examples of the polycarboxylic acid as a superposed component of the crystalline polyester resin include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0160] Polycarboxylic acids may be used together with dicarboxylic acids and trivalent or higher carboxylic acids having a cross-linked structure or a branched structure. Examples of trivalent carboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., having 1 to 5 carbon atoms) alkyl esters.

[0161] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond can be used together with these dicarboxylic acids.

[0162] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0163] Examples of the polyol as a polymerization component of the crystalline polyester resin include aliphatic diols (e.g., linear aliphatic diols having a main chain portion with 7 to 20 carbon atoms). Examples of the aliphatic diol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol.

[0164] As a polyol as a polymerization component of the crystalline polyester resin, a trivalent or higher-valent alcohol having a cross-linked or branched structure may be used together with a diol. Examples of the trivalent or higher-valent alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0165] The polyols may be used alone or in combination of two or more.

[0166] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0167] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Determination of Transition Temperatures of Plastics".

[0168] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.

[0169] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a known production method.

[0170] -Vinyl resin-

[0171] Examples of the vinyl resin include polyolefins, styrene resins, (meth)acrylic resins, and styrene (meth)acrylic resins. Preferred vinyl resins include styrene (meth)acrylic resins. Examples of the styrene (meth)acrylic resin include resins obtained by polymerizing the following styrene monomers and (meth)acrylic monomers.

[0172] Examples of styrene-based monomers include styrene, α-methylstyrene, and vinylnaphthalene; alkyl-substituted styrenes such as 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, and 4-ethylstyrene; halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene, and 4-chlorostyrene; and fluorine-substituted styrenes such as 4-fluorostyrene and 2,5-difluorostyrene. Preferred styrene-based monomers include styrene and α-methylstyrene. These styrene-based monomers may be used alone or in combination of two or more.

[0173] Examples of the (meth)acrylic acid monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, neopentyl (meth)acrylate, and propyl (meth)acrylate. isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, (meth)acrylonitrile, (meth)acrylamide, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.

[0174] As the (meth)acrylic monomer, for example, a lower alkyl (meth)acrylate is preferred. In the lower alkyl (meth)acrylate, "lower alkyl" means a group having 1 to 5 carbon atoms. For example, a "lower alkyl" preferably has 2 to 4 carbon atoms, and more preferably has 3 or 4 carbon atoms.

[0175] Examples of the lower alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, and neopentyl (meth)acrylate. Among these, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and n-butyl (meth)acrylate is particularly preferred.

[0176] The polymerization ratio of the styrene-based monomer to the (meth)acrylic-based monomer (based on mass, styrene-based monomer:(meth)acrylic-based monomer) is, for example, preferably 30:70 to 70:30, more preferably 40:60 to 60:40, and even more preferably 45:55 to 55:45.

[0177] The solubility parameter of the vinyl resin is preferably 8.0 (cal / cm 3 ) 0.5 Above and 11.5 (cal / cm 3 ) 0.5 Below, more preferably 8.5 (cal / cm 3 ) 0.5 Above and 10.5 (cal / cm 3 ) 0.5 Below, more preferably 9.0 (cal / cm 3 ) 0.5 Above and 10.0(cal / cm 3 ) 0.5 the following.

[0178] The solubility parameter of the vinyl resin is a value estimated by the Fedors method.

[0179] -Release agent-

[0180] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0181] The melting temperature of the release agent is, for example, preferably 50° C. or higher and 110° C. or lower, and more preferably 60° C. or higher and 100° C. or lower.

[0182] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Determination of Transition Temperatures of Plastics".

[0183] -Colorant-

[0184] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont Oil Red, pyrazolone red, litho red, rhodamine B Lake, Red Lake C, pigment red, rose Bengal, aniline blue, histidine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; dyes such as acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, nigrosine, polymethine, triphenylmethane, diphenylmethane, and thiazole; and inorganic pigments such as titanium compounds and silica.

[0185] The colorant may be used alone or in combination of two or more.

[0186] The colorant is not limited to a substance that absorbs in the visible light region, and may be, for example, a substance that absorbs in the near-infrared region or a fluorescent colorant.

[0187] Examples of colorants having absorption in the near-infrared region include ammonium salt compounds, naphthalocyanine compounds, squarylium compounds, and crotonate compounds.

[0188] Examples of the fluorescent colorant include those described in paragraph 0027 of JP-A-2021-127431.

[0189] The colorant may be a colorant with a bright finish. Examples of such bright finishes include metal powders such as aluminum, brass, bronze, nickel, stainless steel, and zinc; mica coated with titanium oxide or yellow iron oxide; a flaky inorganic crystal matrix coated with barium sulfate, layered silicates, or layered aluminum silicates; single-crystal plate-like titanium oxide, alkaline carbonates, bismuth oxychloride, natural guanine, flaky glass powder, and metal-evaporated flaky glass powder.

[0190] The colorant may be used alone or in combination of two or more.

[0191] The colorant may be a surface-treated colorant as needed, or may be used together with a dispersant.

[0192] In the present embodiment, the toner particles may or may not contain a colorant. In the present embodiment, the toner particles may contain no colorant, that is, a so-called transparent toner.

[0193] The colorant particle dispersion preferably has a solid content concentration, a hydrogen ion concentration, and a temperature adjusted to 10% by mass, a pH of 6, and a temperature of 25° C., respectively, and a zeta potential measured to be −40 mV or higher and −15 mV or lower.

[0194] When the zeta potential is -40 mV or higher, appropriate aggregation is easily achieved, and uniform adhesion is easily achieved when mixing a dispersion containing the first aggregated particles with a dispersion containing the amorphous polyester resin particles. From this perspective, the zeta potential is more preferably -35 mV or higher, and even more preferably -30 mV or higher.

[0195] When the zeta potential is -15 mV or less, excessive aggregation is less likely to occur, and uniform adhesion is facilitated when mixing a dispersion containing the first aggregated particles with a dispersion containing the amorphous polyester resin particles. From this perspective, the zeta potential is more preferably -20 mV or less, and even more preferably -25 mV or less.

[0196] The zeta potential of the colorant particle dispersion can be controlled by the type of colorant and the type and amount of surfactant.

[0197] The zeta potential of the colorant particle dispersion is measured using electrophoresis (also known as the laser Doppler method). An example of a measuring device is the OTSUKA ELECTRONICS CO., LTD. Zeta Potential Measurement System ELSZ-2000Z or ELSZ-2000ZS. A portion of the colorant particle dispersion is diluted with deionized water to a solids concentration of 10% by mass. The pH is then adjusted to 6 using 0.1 mol / L nitric acid or a 0.1 mol / L sodium hydroxide aqueous solution to prepare the measurement sample. The sample liquid temperature during measurement is 25°C.

[0198] Hereinafter, a dispersion obtained by mixing a plurality of particle dispersions is referred to as a “mixed dispersion.” Polyester resins and vinyl resins are collectively referred to as “binder resins,” and polyester resin particles and vinyl resin particles are collectively referred to as “binder resin particles.”

[0199] The mass ratio of the particles contained in the mixed dispersion is preferably within the following range, for example.

[0200] When the mixed dispersion contains release agent particles, the mass ratio of the binder resin particles to the release agent particles is, for example, preferably binder resin particles:release agent particles = 100:1 to 100:40, more preferably 100:2 to 100:30, and even more preferably 100:5 to 100:20.

[0201] When the mixed dispersion contains colorant particles, the mass ratio of the binder resin particles to the colorant particles is, for example, preferably binder resin particles:colorant particles = 100:1 to 100:100, more preferably 100:2 to 100:40, and even more preferably 100:5 to 100:20.

[0202] After mixing the plurality of particle dispersions, the pH of the mixed dispersion is preferably adjusted to, for example, 3 to 4. Examples of methods for adjusting the pH of the mixed dispersion include adding an acidic aqueous solution such as nitric acid, hydrochloric acid, or sulfuric acid.

[0203] The first coagulation step includes, for example, the following steps:

[0204] adding a coagulant to the mixed dispersion while stirring the mixed dispersion; and

[0205] After the coagulant is added to the mixed dispersion, the mixed dispersion is heated while stirring the mixed dispersion to increase the temperature of the mixed dispersion.

[0206] Examples of the coagulant include surfactants having a polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher-valent metal complexes. The coagulant may be used alone or in combination of two or more.

[0207] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0208] The coagulant is preferably a divalent or higher metal salt compound, more preferably a trivalent metal salt compound, and still more preferably a trivalent inorganic aluminum salt compound. Examples of the trivalent inorganic aluminum salt compound include aluminum chloride, aluminum sulfate, polyaluminum chloride, and polyaluminum hydroxide.

[0209] The amount of coagulant added is not limited. When a trivalent metal salt compound is used as the coagulant, the amount of the trivalent metal salt compound added is, for example, preferably from 0.01 to 10 parts by mass, more preferably from 0.05 to 5 parts by mass, and even more preferably from 0.1 to 3 parts by mass, relative to 100 parts by mass of the binder resin.

[0210] The temperature reached when the mixed dispersion is heated is preferably a temperature based on the glass transition temperature (Tg) of the binder resin particles, for example, (Tg-30°C) or higher and (Tg°C) or lower.

[0211] When the mixed dispersion contains a plurality of binder resin particles having different Tgs, the lowest temperature among the respective Tgs is defined as the Tg in the aggregation step.

[0212] [Second Coagulation Step]

[0213] The second aggregation step is a step of mixing a dispersion containing first aggregated particles with a dispersion containing at least amorphous polyester resin particles, and causing at least the amorphous polyester resin particles to adhere to the surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles.

[0214] Hereinafter, the dispersion containing at least the amorphous polyester resin particles used in the second aggregation step is referred to as a "shell-forming dispersion."

[0215] The temperature (°C) of the dispersion containing the first aggregated particles when the dispersion containing the first aggregated particles and the shell-forming dispersion begin to be mixed is Tc related to formula (1), and the solid content concentration (mass %) of the dispersion containing the first aggregated particles is Wc related to formula (4).

[0216] The temperature (°C) of the shell-forming dispersion when the dispersion containing the first aggregated particles and the shell-forming dispersion are mixed is Ts related to formula (2), and the solid content concentration (mass %) of the shell-forming dispersion is Ws related to formula (5).

[0217] When the dispersion contains a surfactant, the surfactant is also contained in the solid content of the dispersion.

[0218] When the second aggregation step is started, the temperature of the dispersion containing the first aggregated particles and the temperature of the shell-forming dispersion are adjusted so as to satisfy the equations (1) and (2).

[0219] When the second aggregation step is started, for example, the solid content concentration of the dispersion containing the first aggregated particles and the solid content concentration of the shell-forming dispersion are preferably adjusted so as to satisfy equations (4) and (5).

[0220] One embodiment of the shell-forming dispersion includes a dispersion containing amorphous polyester resin particles and release agent particles. When this dispersion is subjected to the second aggregation step, a shell containing the amorphous polyester resin and the release agent is formed.

[0221] When a dispersion containing amorphous polyester resin particles and release agent particles is used as the shell-forming dispersion, the temperature of the dispersion is Ts related to formula (2), and the solid content concentration of the dispersion is Ws related to formula (5).

[0222] The shell-forming dispersion may be the amorphous polyester resin particle dispersion itself, or a dispersion obtained by preliminarily mixing the amorphous polyester resin particle dispersion and the release agent particle dispersion.

[0223] The form, materials, and production method of the amorphous polyester resin particle dispersion and the release agent particle dispersion are the same as those used in the first coagulation step. The solids concentration and temperature of the amorphous polyester resin particle dispersion and the release agent particle dispersion used in the first coagulation step can be adjusted before the dispersion is subjected to the second coagulation step.

[0224] Tgs related to formula (1), that is, the glass transition temperature of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion, is, for example, preferably 50° C. or higher, more preferably 52° C. or higher, and even more preferably 54° C. or higher.

[0225] Tgs related to formula (1), that is, the glass transition temperature of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion is, for example, preferably 70° C. or lower, more preferably 68° C. or lower, and even more preferably 65° C. or lower.

[0226] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition onset temperature" method described in JIS K7121-1987 "Plastics - Determination of Transition Temperatures".

[0227] The amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion preferably has an acid value of, for example, 8 mgKOH / g or more and 16 mgKOH / g or less.

[0228] When the acid value of the amorphous polyester resin is 8 mgKOH / g or greater, excessive aggregation is less likely to occur, and uniform adhesion is facilitated when mixing a dispersion containing the first aggregated particles with a dispersion containing the amorphous polyester resin particles. From this perspective, the acid value of the amorphous polyester resin is more preferably 8.5 mgKOH / g or greater, and even more preferably 9 mgKOH / g or greater.

[0229] When the acid value of the amorphous polyester resin is 16 mgKOH / g or less, it tends to exhibit appropriate cohesion, and when a dispersion containing the first coagulated particles and a dispersion containing the amorphous polyester resin particles are mixed, uniform adhesion is facilitated. From this perspective, the acid value of the amorphous polyester resin is more preferably 15 mgKOH / g or less, and even more preferably 14 mgKOH / g or less.

[0230] The acid value of the amorphous polyester resin is determined by the neutralization titration method specified in JIS K0070-1992.

[0231] The solubility parameter of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion is preferably 8.5 (cal / cm 3 ) 0.5 Above and 11.5 (cal / cm 3 ) 0.5 Below, more preferably 9.0 (cal / cm 3 ) 0.5 Above and 10.5 (cal / cm 3 ) 0.5 Below, more preferably 9.0 (cal / cm 3 ) 0.5 Above and 10.0(cal / cm 3 ) 0.5 the following.

[0232] The solubility parameter of the amorphous polyester resin is a value estimated by the Fedors method.

[0233] When the dispersion in the first coagulation step is a dispersion containing vinyl resin particles, the difference in solubility parameter between the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second coagulation step is preferably 1.0 (cal / cm 3 ) 0.5 The solubility parameters of the vinyl resin and the solubility parameters of the amorphous polyester resin are values ​​estimated by the Fedors method.

[0234] If the above difference is 1.0 (cal / cm 3 ) 0.5 Below, the amorphous polyester resin particles are easily attached to the surface of the first aggregated particles containing vinyl resin particles. From this viewpoint, the above difference is more preferably 0.8 (cal / cm 3 ) 0.5 Below, more preferably 0.5 (cal / cm 3 ) 0.5Below, most preferably 0 (cal / cm 3 ) 0.5 .

[0235] The second aggregation step is performed, for example, by adding the shell-forming dispersion while stirring the dispersion containing the first aggregated particles, and then heating the dispersion while stirring. Stirring is performed with a stirring power that satisfies equation (3). The temperature reached by the heated dispersion is based on the glass transition temperature (Tgs) of the amorphous polyester resin that forms the shell, and is preferably, for example, not less than (Tgs-20°C) and not more than (Tgs-10°C).

[0236] After the second aggregated particles have grown to a predetermined size and before the heating step of the fusion step, a chelating agent for the flocculant used in the first aggregation step may be added to the dispersion containing the second aggregated particles to stop the growth of the second aggregated particles.

[0237] Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0238] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the binder resin particles.

[0239] After the second aggregated particles have grown to a predetermined size, and before the heating step of combining the particles, the pH of the dispersion containing the second aggregated particles may be increased for the purpose of stopping the growth of the second aggregated particles.

[0240] Examples of methods for increasing the pH of the dispersion containing the second aggregated particles include adding at least one selected from the group consisting of aqueous solutions of alkali metal hydroxides and aqueous solutions of alkaline earth metal hydroxides.

[0241] The ultimate pH of the dispersion containing the second aggregated particles is preferably, for example, 8 or more and 10 or less.

[0242] [Combination process]

[0243] The agglomeration step is a step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles into a fusion body to form toner particles.

[0244] The reaching temperature of the dispersion containing the second aggregated particles is preferably, for example, not less than the glass transition temperature (Tg) of the amorphous polyester resin particles, and specifically, preferably a temperature 10° C. to 30° C. higher than the Tg of the amorphous polyester resin particles.

[0245] When a plurality of amorphous polyester resin particles having different Tgs are used in the first and second coagulation steps, the highest temperature among the respective Tgs is defined as the glass transition temperature in the combining step.

[0246] After the combining step, the toner particles in the dispersion are subjected to known washing, solid-liquid separation, and drying steps to obtain dry toner particles. For the sake of chargeability, the washing step is preferably performed by, for example, thorough displacement washing with deionized water. For the sake of productivity, the solid-liquid separation step is preferably performed by, for example, suction filtration or pressure filtration. For the sake of productivity, the drying step is preferably performed by, for example, freeze drying, airflow drying, fluidized bed drying, or vibrating fluidized bed drying.

[0247] [Process of adding external additives]

[0248] The method for producing the toner according to the present embodiment preferably includes, for example, a step of adding an external additive to the toner particles.

[0249] The external additive is added to the toner particles by mixing the dry toner particles and the external additive. Mixing is performed, for example, using a V-blender, Henschel mixer, or Lödige mixer. Furthermore, if necessary, a vibrating screen or wind screen can be used to remove coarse toner particles.

[0250] Examples of external additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0251] For the surface of the inorganic particles as an external additive, for example, hydrophobization treatment is preferably implemented.Hydrophobic treatment is for example carried out by impregnating the inorganic particles in a hydrophobization treatment agent.Hydrophobic treatment agent is not particularly limited, for example, silane coupling agent, silicone oil, titanate coupling agent, aluminum coupling agent etc. can be cited.They can be used alone or in combination of two or more.

[0252] Typically, the amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0253] Examples of external additives include resin particles (polystyrene, polymethyl methacrylate, melamine resin, and other resin particles), cleaning aids (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight substances), and the like.

[0254] The amount of the external additive added is, for example, preferably from 0.01 mass % to 5 mass %, and more preferably from 0.01 mass % to 2 mass %, relative to the mass of the toner particles.

[0255] <Toner for electrostatic latent image development>

[0256] The toner produced by the production method according to this embodiment is preferably an externally added toner in which an external additive is added to toner particles, for example. The form of the external additive is as described above.

[0257] The toner particles have a core / shell structure comprising a core containing at least a polyester resin and a shell containing at least an amorphous polyester resin. The toner particles may contain a vinyl resin in the core. The toner particles may contain a release agent in the core. The toner particles may contain a release agent in the shell. The toner particles may contain a colorant in the core.

[0258] The total content of the polyester resin relative to the entire toner is, for example, preferably 40 mass % to 95 mass %, more preferably 50 mass % to 90 mass %, and further preferably 60 mass % to 85 mass %.

[0259] When the toner particles contain a crystalline polyester resin, the content of the crystalline polyester resin is, for example, preferably 3% by mass or more and 30% by mass or less, and more preferably 8% by mass or more and 20% by mass or less, based on the total binder resin.

[0260] When the toner particles contain a vinyl resin, the content of the vinyl resin is, for example, preferably from 1 mass % to 30 mass % of the total binder resin, and more preferably from 3 mass % to 20 mass %.

[0261] When the toner contains a releasing agent, the content of the releasing agent is, for example, preferably 1 mass % or more and 20 mass % or less, and more preferably 5 mass % or more and 15 mass % or less, based on the entire toner.

[0262] When the toner contains a colorant, the content of the colorant is, for example, preferably 1 mass % or more and 30 mass % or less, and more preferably 3 mass % or more and 15 mass % or less, based on the entire toner.

[0263] The volume average particle size of the toner is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less. The volume average particle size of the toner is measured as follows.

[0264] The particle size distribution of the toner is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) and an ISOTON-II (manufactured by Beckman Coulter, Inc.) for the electrolyte. During the measurement, as a dispersant, a measurement sample of 0.5 mg or more and 50 mg or less is added to 2 ml of a 5% by mass aqueous solution of a surfactant (for example, preferably sodium alkylbenzene sulfonate). This is added to an electrolyte of 100 ml or more and 150 ml or less. The electrolyte in which the sample is suspended is dispersed for 1 minute by an ultrasonic disperser, and the particle size distribution of particles with a particle size range of 2 μm or more and 60 μm or less is measured using a Coulter Multisizer II with a hole of 100 μm in diameter. The number of particles to be sampled is 50,000. The particle size distribution is depicted from the smaller diameter side, and the particle size when accumulated to 50% is set as the volume average particle size D50v.

[0265] The average circularity of the toner is, for example, preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.

[0266] The average circularity of the toner is (the circumference of a circle having the same area as the particle projected image) / (the circumference of the particle projected image). This is determined by sampling 3,500 particles using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation).

[0267] <Developer>

[0268] The toner produced by the production method according to this embodiment may be used as a single-component developer, or may be mixed with a carrier and used as a two-component developer.

[0269] The carrier is not particularly limited, and known carriers may be used. Examples of the carrier include coated carriers in which the surface of a core material composed of magnetic powder is coated with a resin; magnetic powder-dispersed carriers in which magnetic powder is dispersed in a matrix resin; and resin-impregnated carriers in which porous magnetic powder is impregnated with a resin.

[0270] The magnetic powder dispersed carrier or the resin impregnated carrier may be a carrier having constituent particles of the carrier as a core material and the surface of the core material coated with a resin.

[0271] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0272] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymers, styrene-acrylate copolymers, linear silicone resins containing organosiloxane bonds or modified products thereof, fluororesins, polyesters, polycarbonates, phenolic resins, and epoxy resins. The coating resin and matrix resin may contain other additives such as conductive particles. Examples of conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0273] In order to coat the surface of the core material with resin, a method of coating with a coating layer formed by dissolving a coating resin and various additives (used as needed) in an appropriate solvent can be cited. There is no particular limitation on the solvent, and the solvent can be selected based on the type of resin used and coating suitability.

[0274] Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution; a spraying method in which the coating layer forming solution is sprayed on the surface of the core material; a fluidized bed method in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and then the solvent is removed; etc.

[0275] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0276] Example

[0277] Hereinafter, embodiments of the present invention will be described in detail based on examples, but the embodiments of the present invention are not limited to these examples.

[0278] In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0279] In the following description, unless otherwise specified, synthesis, production, handling, measurement, etc. were performed at room temperature (25°C ± 3°C).

[0280] <Preparation of amorphous polyester resin particle dispersion>

[0281] [Preparation of amorphous polyester resin particle dispersion (1)]

[0282] -Synthesis of amorphous polyester resin-

[0283] The following materials were prepared.

[0284] Terephthalic acid: 69 parts

[0285] Tricarboxymethane: 31 parts

[0286] Ethylene glycol: 40 parts

[0287] 1,5-Pentanediol: 45 parts

[0288] The above materials were placed in a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column. The temperature was raised to 220°C over 1 hour under a nitrogen flow, and 1 part of tetraethoxytitanium was added to a total of 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 240°C over 0.5 hours. After a dehydration condensation reaction was continued at 240°C for 1 hour, the reactant was cooled. In this way, an amorphous polyester resin (1) having an acid value of 12.1 mgKOH / g, a weight-average molecular weight of 127,000, and a glass transition temperature of 56°C was obtained.

[0289] -Emulsification and dispersion of amorphous polyester resin-

[0290] 100 parts of amorphous polyester resin (1), 70 parts of ethyl acetate, and 15 parts of isopropyl alcohol were placed in a reaction tank equipped with a stirrer, a capacitor, a heater, and a thermometer. The temperature in the reaction tank was raised to 50°C, and the resin was dissolved in the organic solvent while stirring for 30 minutes while maintaining the temperature at 50°C. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, followed by gradual addition of 330 parts of deionized water at a temperature of 40°C, thereby obtaining an emulsion. The pressure in the reaction tank was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: NEOGEN RK, DKS Co. Ltd., 20% aqueous solution) was added to obtain an amorphous polyester resin particle dispersion (1) having a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (1) was 180 nm.

[0291] In the examples described below, when the amorphous polyester resin particle dispersion (1) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary, and the solid content concentration was adjusted as shown in Table 1 to prepare a shell-forming dispersion.

[0292] [Preparation of amorphous polyester resin particle dispersion (2)]

[0293] -Synthesis of amorphous polyester resin-

[0294] The following materials were prepared.

[0295] Terephthalic acid: 69 parts

[0296] Tricarboxymethane: 31 parts

[0297] Ethylene glycol: 48 parts

[0298] 1,5-Pentanediol: 47 parts

[0299] The above materials were placed in a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column. The temperature was raised to 220°C over 1 hour under a nitrogen flow, and 1 part of tetraethoxytitanium was added to a total of 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 240°C over 0.5 hours. After a dehydration condensation reaction was continued at 240°C for 1 hour, the reactant was cooled. In this way, an amorphous polyester resin (2) having an acid value of 8.0 mgKOH / g, a weight-average molecular weight of 139,000, and a glass transition temperature of 56°C was obtained.

[0300] -Emulsification and dispersion of amorphous polyester resin-

[0301] 100 parts of amorphous polyester resin (2), 70 parts of ethyl acetate, and 15 parts of isopropyl alcohol were placed in a reaction tank equipped with a stirrer, a capacitor, a heater, and a thermometer. The temperature in the reaction tank was raised to 50°C, and the resin was dissolved in the organic solvent while stirring for 30 minutes while maintaining the temperature at 50°C. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, followed by gradual addition of 330 parts of deionized water at a temperature of 40°C, thereby obtaining an emulsion. The pressure in the reaction tank was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: NEOGEN RK, DKS Co. Ltd., 20% aqueous solution) was added to obtain an amorphous polyester resin particle dispersion (2) having a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (2) was 180 nm.

[0302] In the examples described below, when the amorphous polyester resin particle dispersion (2) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary, and the solid content concentration was adjusted as shown in Table 1 to prepare a shell-forming dispersion.

[0303] [Preparation of amorphous polyester resin particle dispersion (3)]

[0304] -Synthesis of amorphous polyester resin-

[0305] The following materials were prepared.

[0306] Terephthalic acid: 69 parts

[0307] Tricarboxymethane: 31 parts

[0308] Ethylene glycol: 36 parts

[0309] 1,5-Pentanediol: 39 parts

[0310] The above materials were placed in a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column. The temperature was raised to 220°C over 1 hour under a nitrogen flow, and 1 part of tetraethoxytitanium was added to a total of 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 240°C over 0.5 hours. After a dehydration condensation reaction was continued at 240°C for 1 hour, the reactant was cooled. In this way, an amorphous polyester resin (3) having an acid value of 16.0 mgKOH / g, a weight-average molecular weight of 116,000, and a glass transition temperature of 56°C was obtained.

[0311] -Emulsification and dispersion of amorphous polyester resin-

[0312] 100 parts of amorphous polyester resin (3), 70 parts of ethyl acetate, and 15 parts of isopropyl alcohol were placed in a reaction tank equipped with a stirrer, a capacitor, a heater, and a thermometer. The temperature in the reaction tank was raised to 50°C, and the resin was dissolved in the organic solvent while stirring for 30 minutes while maintaining the temperature at 50°C. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, followed by gradual addition of 330 parts of deionized water at 40°C to obtain an emulsion. The pressure in the reaction tank was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: NEOGEN RK, DKS Co. Ltd., 20% aqueous solution) was added to obtain an amorphous polyester resin particle dispersion (3) with a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (3) was 180 nm.

[0313] In the examples described below, when the amorphous polyester resin particle dispersion (3) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary, and the solid content concentration was adjusted as shown in Table 1 to prepare a shell-forming dispersion.

[0314] <Preparation of Crystalline Polyester Resin Particle Dispersion (1)>

[0315] -Synthesis of Crystalline Polyester Resin-

[0316] The following materials were prepared.

[0317] Succinic acid: 48 mol parts

[0318] 1,5-Pentanediol: 52 mol parts

[0319] Dibutyltin oxide: 0.08 mol parts

[0320] The above materials were placed in a stirring tank and mixed. The temperature in the stirring layer was raised to 220° C. under a reduced pressure atmosphere, and a dehydration condensation reaction was carried out for 6 hours, thereby obtaining a crystalline polyester resin (1).

[0321] -Dispersion of crystalline polyester resin-

[0322] The following materials were prepared.

[0323] Crystalline polyester resin (1): 80 parts

[0324] Deionized water: 720 parts

[0325] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co., Ltd., 20% aqueous solution): 1.8 parts

[0326] The above materials were mixed and heated to 55°C, dispersed using a homogenizer (ULTRA TURRAX T50, IKA), and then dispersed using a pressure-dispensing homogenizer (Manton-Gaulin High-Pressure Homogenizer, Gaulin). When the volume average particle size reached 160 nm, the particles were recovered to obtain a crystalline polyester resin particle dispersion (1) having a solid content concentration of 10%.

[0327] <Preparation of Vinyl Resin Particle Dispersion>

[0328] [Preparation of Vinyl Resin Particle Dispersion (1)]

[0329] -Preparation of Emulsion (1-1)-

[0330] The following materials were prepared.

[0331] Styrene: 5.5 parts

[0332] n-Butyl acrylate: 4.5 parts

[0333] Dodecanethiol: 0.05 parts

[0334] Deionized water: 500 parts

[0335] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0336] The above materials were placed in a reactor equipped with a reflux cooling tube, a stirrer, a nitrogen inlet tube, and a monomer dropping port, and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (1-1).

[0337] -Preparation of Emulsion (1-2)-

[0338] The following materials were prepared.

[0339] Styrene: 385 parts

[0340] n-Butyl acrylate: 203 parts

[0341] · Dodecanethiol: 2 parts

[0342] Deionized water: 846 parts

[0343] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0344] The above materials were placed in a reactor equipped with a stirrer and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (1-2).

[0345] -Formation of Vinyl Resin Particles-

[0346] After obtaining the emulsion (1-1), nitrogen substitution was performed inside the reactor. Furthermore, while introducing nitrogen into the reactor, the temperature was raised to 75°C, 50 parts of a 10% aqueous solution of ammonium persulfate were added, and the mixture was maintained for 20 minutes. Next, while the temperature was maintained at 75°C and stirring was continued, the emulsion (1-2) was added dropwise from the monomer addition port of the reactor over a period of 2 hours. 30 minutes after the end of the dropwise addition of the emulsion (1-2), 5 parts of a 10% aqueous solution of ammonium persulfate were added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. The temperature was maintained at 75°C while stirring was continued for 1.5 hours. Then, the inside of the reactor was cooled to room temperature, the solid content concentration was adjusted to 30%, and a vinyl resin particle dispersion (1) was obtained. The volume average particle size of the particles in the vinyl resin particle dispersion (1) was 140 nm.

[0347] [Preparation of Vinyl Resin Particle Dispersion (2)]

[0348] -Preparation of Emulsion (2-1)-

[0349] The following materials were prepared.

[0350] Styrene: 6 parts

[0351] n-Butyl acrylate: 4 parts

[0352] Dodecanethiol: 0.05 parts

[0353] Deionized water: 500 parts

[0354] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0355] The above materials were placed in a reactor equipped with a reflux cooling tube, a stirrer, a nitrogen inlet tube, and a monomer dropping port, and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (2-1).

[0356] -Preparation of Emulsion (2-2)-

[0357] The following materials were prepared.

[0358] Styrene: 415 parts

[0359] n-Butyl acrylate: 173 parts

[0360] · Dodecanethiol: 2 parts

[0361] Deionized water: 846 parts

[0362] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0363] The above materials were placed in a reactor equipped with a stirrer and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (2-2).

[0364] -Formation of Vinyl Resin Particles-

[0365] After obtaining the emulsion (2-1), nitrogen substitution was performed inside the reactor. Furthermore, while introducing nitrogen into the reactor, the temperature was raised to 75°C, 50 parts of a 10% aqueous solution of ammonium persulfate were added, and the mixture was maintained for 20 minutes. Next, while the temperature was maintained at 75°C and stirring was continued, the emulsion (2-2) was added dropwise from the monomer addition port of the reactor over a period of 2 hours. 30 minutes after the end of the dropwise addition of the emulsion (2-2), 5 parts of a 10% aqueous solution of ammonium persulfate were added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. The temperature was maintained at 75°C while stirring was continued for 1.5 hours. Then, the inside of the reactor was cooled to room temperature, the solid content concentration was adjusted to 30%, and a vinyl resin particle dispersion (2) was obtained. The volume average particle size of the particles in the vinyl resin particle dispersion (2) was 140 nm.

[0366] [Preparation of Vinyl Resin Particle Dispersion (3)]

[0367] -Preparation of Emulsion (3-1)-

[0368] The following materials were prepared.

[0369] Styrene: 8 parts

[0370] n-Butyl acrylate: 2 parts

[0371] Dodecanethiol: 0.05 parts

[0372] Deionized water: 500 parts

[0373] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0374] The above materials were placed in a reactor equipped with a reflux cooling tube, a stirrer, a nitrogen inlet tube, and a monomer dropping port, and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (3-1).

[0375] -Preparation of Emulsion (3-2)-

[0376] The following materials were prepared.

[0377] Styrene: 470 parts

[0378] n-Butyl acrylate: 118 parts

[0379] · Dodecanethiol: 2 parts

[0380] Deionized water: 846 parts

[0381] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0382] The above materials were placed in a reactor equipped with a stirrer and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (3-2).

[0383] -Formation of Vinyl Resin Particles-

[0384] After obtaining the emulsion (3-1), nitrogen substitution was performed inside the reactor. Furthermore, while introducing nitrogen into the reactor, the temperature was raised to 75°C, 50 parts of a 10% aqueous solution of ammonium persulfate were added, and the mixture was maintained for 20 minutes. Next, while the temperature was maintained at 75°C and stirring was continued, the emulsion (3-2) was added dropwise from the monomer addition port of the reactor over a period of 2 hours. 30 minutes after the addition of the emulsion (3-2) was completed, 5 parts of a 10% aqueous solution of ammonium persulfate were added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. The temperature was maintained at 75°C while stirring was continued for 1.5 hours. Then, the inside of the reactor was cooled to room temperature, the solid content concentration was adjusted to 30%, and a vinyl resin particle dispersion (3) was obtained. The volume average particle size of the particles in the vinyl resin particle dispersion (3) was 140 nm.

[0385] [Preparation of Vinyl Resin Particle Dispersion (4)]

[0386] -Preparation of Emulsion (4-1)-

[0387] The following materials were prepared.

[0388] Styrene: 8.5 parts

[0389] n-Butyl acrylate: 1.5 parts

[0390] Dodecanethiol: 0.05 parts

[0391] Deionized water: 500 parts

[0392] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0393] The above materials were placed in a reactor equipped with a reflux cooling tube, a stirrer, a nitrogen inlet tube, and a monomer dropping port, and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (4-1).

[0394] -Preparation of Emulsion (4-2)-

[0395] The following materials were prepared.

[0396] Styrene: 492 parts

[0397] n-Butyl acrylate: 96 parts

[0398] · Dodecanethiol: 2 parts

[0399] Deionized water: 846 parts

[0400] Anionic surfactant (trade name: NEWCOL271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0401] The above materials were placed in a reactor equipped with a stirrer and stirred at room temperature to emulsify the mixture, thereby obtaining an emulsion (4-2).

[0402] -Formation of Vinyl Resin Particles-

[0403] After obtaining the emulsion (4-1), nitrogen substitution was performed inside the reactor. Furthermore, while introducing nitrogen into the reactor, the temperature was raised to 75°C, 50 parts of a 10% aqueous solution of ammonium persulfate were added, and the mixture was maintained for 20 minutes. Next, while the temperature was maintained at 75°C and stirring was continued, the emulsion (4-2) was added dropwise from the monomer addition port of the reactor over a period of 2 hours. 30 minutes after the addition of the emulsion (4-2) was completed, 5 parts of a 10% aqueous solution of ammonium persulfate were added, and further 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. The temperature was maintained at 75°C while stirring was continued for 1.5 hours. Then, the inside of the reactor was cooled to room temperature, the solid content concentration was adjusted to 30%, and a vinyl resin particle dispersion (4) was obtained. The volume average particle size of the particles in the vinyl resin particle dispersion (4) was 140 nm.

[0404] <Preparation of Release Agent Particle Dispersion (1)>

[0405] The following materials were prepared.

[0406] Paraffin wax (melting point 92°C, trade name: FNP92, NIPPON SEIRO CO., LTD.): 87 parts

[0407] Deionized water: 200 parts

[0408] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 3 parts

[0409] The above materials were mixed and heated to 95°C, dispersed using a homogenizer (ULTRA TURRAX T50, IKA), and then dispersed using a pressure-dispensing homogenizer (Manton-Gaulin High-Pressure Homogenizer, Gaulin). When the volume average particle size reached 190 nm, the particles were recovered to obtain a release agent particle dispersion (1) having a solids concentration of 30%.

[0410] <Preparation of Colorant Particle Dispersion>

[0411] [Preparation of Colorant Particle Dispersion (1)]

[0412] The following materials were prepared.

[0413] Carbon black (trade name: #25B, Mitsubishi Chemical Corporation): 20 parts

[0414] Deionized water: 80 parts

[0415] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 2 parts

[0416] The above materials were mixed and dispersed using a high-pressure impact disperser (trade name: ULTIMAIZER HJP30006, SUGINOMACHINE LIMITED CO., LTD.) and recovered when the volume average particle size reached 180 nm to obtain a colorant particle dispersion (1) having a solid content concentration of 20%.

[0417] A portion of the colorant particle dispersion (1) was collected and adjusted to a solid content concentration of 10%, a pH of 6, and a temperature of 25° C. The zeta potential was measured using a zeta potential measurement system (trade name: ELSZ-2000ZS, OTSUKA ELECTRONICSCO., LTD.). The zeta potential was -25 mV.

[0418] [Preparation of Colorant Particle Dispersion (2)]

[0419] The following materials were prepared.

[0420] Carbon black (trade name: #25B, Mitsubishi Chemical Corporation): 20 parts

[0421] Deionized water: 80 parts

[0422] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 6 parts

[0423] The above materials were mixed and dispersed using a high-pressure impact disperser (trade name: ULTIMAIZER HJP30006, SUGINOMACHINE LIMITED CO., LTD.) and recovered when the volume average particle size reached 250 nm to obtain a colorant particle dispersion (2) having a solid content concentration of 20%.

[0424] A portion of the colorant particle dispersion (2) was collected and adjusted to a solid content concentration of 10%, a pH of 6, and a temperature of 25° C. The zeta potential was measured using a zeta potential measurement system (trade name: ELSZ-2000ZS, OTSUKA ELECTRONICSCO., LTD.). The zeta potential was -45 mV.

[0425] [Preparation of Colorant Particle Dispersion (3)]

[0426] The following materials were prepared.

[0427] Carbon black (trade name: #25B, Mitsubishi Chemical Corporation): 20 parts

[0428] Deionized water: 80 parts

[0429] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 5 parts

[0430] The above materials were mixed and dispersed using a high-pressure impact disperser (trade name: ULTIMAIZER HJP30006, SUGINOMACHINE LIMITED CO., LTD.) and recovered when the volume average particle size reached 220 nm to obtain a colorant particle dispersion (3) having a solid content concentration of 20%.

[0431] A portion of the colorant particle dispersion (3) was collected and adjusted to a solid content concentration of 10%, a pH of 6, and a temperature of 25° C. The zeta potential was measured using a zeta potential measurement system (trade name: ELSZ-2000ZS, OTSUKA ELECTRONICSCO., LTD.). The zeta potential was -40 mV.

[0432] [Preparation of Colorant Particle Dispersion (4)]

[0433] The following materials were prepared.

[0434] Carbon black (trade name: #25B, Mitsubishi Chemical Corporation): 20 parts

[0435] Deionized water: 80 parts

[0436] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 1.5 parts

[0437] The above materials were mixed and dispersed using a high-pressure impact disperser (trade name: ULTIMAIZER HJP30006, SUGINOMACHINE LIMITED CO., LTD.) and recovered when the volume average particle size reached 130 nm to obtain a colorant particle dispersion (4) having a solid content concentration of 20%.

[0438] A portion of the colorant particle dispersion (4) was collected and adjusted to a solid content concentration of 10%, a pH of 6, and a temperature of 25° C. The zeta potential was measured using a zeta potential measurement system (trade name: ELSZ-2000ZS, OTSUKA ELECTRONICSCO., LTD.). The zeta potential was -15 mV.

[0439] [Preparation of Colorant Particle Dispersion (5)]

[0440] The following materials were prepared.

[0441] Carbon black (trade name: #25B, Mitsubishi Chemical Corporation): 20 parts

[0442] Deionized water: 80 parts

[0443] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 1 part

[0444] The above materials were mixed and dispersed using a high-pressure impact disperser (trade name: ULTIMAIZER HJP30006, SUGINOMACHINE LIMITED CO., LTD.) and recovered when the volume average particle size reached 110 nm to obtain a colorant particle dispersion (5) having a solid content concentration of 20%.

[0445] A portion of the colorant particle dispersion (5) was collected and adjusted to a solid content concentration of 10%, a pH of 6, and a temperature of 25° C. The zeta potential was measured using a zeta potential measurement system (trade name: ELSZ-2000ZS, OTSUKA ELECTRONICSCO., LTD.). The zeta potential was -12 mV.

[0446] In the following examples and comparative examples, the target charge amount of the developer is -43 μC / g, and the target particle size of the toner particles is 5.0 μm.

[0447] <Example 1>

[0448] [Preparation of Toner Particles]

[0449] The following materials were prepared.

[0450] Deionized water: 235 parts

[0451] Amorphous polyester resin particle dispersion (1): 170 parts

[0452] Crystalline polyester resin particle dispersion (1): 100 parts

[0453] Release agent particle dispersion (1): 25 parts

[0454] Colorant particle dispersion (1): 50 parts

[0455] Anionic surfactant (TaycaPower): 3.0 parts

[0456] -First Coagulation Step-

[0457] The above materials were placed in a stirred tank equipped with a jacket and stirring blades to prepare a mixed dispersion with a solid content concentration of 15%. 0.1N nitric acid was added to the mixed dispersion to adjust the pH to 3.5. Next, an aqueous solution of aluminum sulfate (2 parts aluminum sulfate dissolved in 30 parts deionized water) was added and dispersed using a homogenizer. The solution in the stirred tank was then heated to 45°C to form first agglomerated particles. The solution temperature was maintained at 45°C until the volume average particle size of the first agglomerated particles reached 4.0 μm.

[0458] -Second Coagulation Step-

[0459] The temperature and concentration of the amorphous polyester resin particle dispersion (1) were adjusted to prepare a shell-forming dispersion having the temperature Ts and concentration Ws shown in Table 1.

[0460] While maintaining the liquid temperature in the stirring tank (i.e., the temperature Tc of the dispersion containing the first aggregated particles) at 45°C, 120 parts of the shell-forming dispersion were added to the stirring tank. 3 Stirring was continued for 30 minutes to form second aggregated particles. 20 parts of a 10% aqueous solution of NTA (nitrilotriacetic acid) metal salt (trade name: CHELEST 70, CHELEST CORPORATION) was added to the stirring tank, and 1N aqueous sodium hydroxide solution was added to adjust the pH to 9.0 to stop the growth of the second aggregated particles.

[0461] -Merge process-

[0462] One part of anionic surfactant (Tayca Power) was added to the stirring tank, and the mixture was heated to 85° C. while being continuously stirred and maintained for 5 hours, and then cooled to 20° C. at a rate of 20° C. / min.

[0463] The toner particle dispersion was placed in a filter press (manufactured by Tokyo Engineering Co., Ltd.) and squeezed at a pressure of 0.4 MPa to form a filter cake. Water, equivalent to 1500% of the filter cake volume, was passed through the filter cake to wash it. The washed filter cake was dried using an airflow dryer, and the dried product was sieved to obtain toner particles (1).

[0464] [Production of external colorant]

[0465] 2 parts of hydrophobic silica particles (product code: RY50, NIPPONAEROSIL CO., LTD.) were added to 100 parts of the toner particles (1), mixed at 10,000 rpm for 30 seconds using a sample mill, and then sieved with a vibrating sieve having an aperture of 45 μm to obtain an externally added toner.

[0466] [Production of developer]

[0467] 8 parts of the external toner and 92 parts of the following carrier (1) were placed in a V mixer and stirred for 20 minutes, and then sieved with a sieve having an aperture of 212 μm to obtain a developer.

[0468] -Preparation of carrier (1)-

[0469] 14 parts of toluene, 5 parts of polymethyl methacrylate (weight-average molecular weight: 75,000), and 0.2 parts of carbon black (product code: VXC-72, Cabot Corporation) were placed in a sand mill and dispersed to prepare a dispersion. The dispersion and 100 parts of ferrite particles (average particle size: 35 μm) were placed in a vacuum degassing kneader and dried under reduced pressure while stirring to obtain a carrier (1).

[0470] <Example 2 to Example 4>

[0471] The same procedure as in Example 1 was followed, except that the temperature Tc and concentration Wc of the first aggregated particle dispersion used in the second aggregation step, and the temperature Ts and concentration Ws of the shell-forming dispersion (amorphous polyester resin particle dispersion) were changed as shown in Table 1 to produce toner particles, an externally added toner, and a developer.

[0472] <Example 5-Example 6>

[0473] The same procedure as in Example 1 was followed, except that the temperature Tc of the first aggregated particle dispersion and the temperature Ts of the shell-forming dispersion (amorphous polyester resin particle dispersion) used in the second aggregation step were changed as shown in Table 1. Toner particles, an externally added toner, and a developer were prepared.

[0474] <Example 7-Example 8>

[0475] The same procedure as in Example 1 was carried out except that the stirring power per unit volume (P-P0) in the second aggregation step was changed as shown in Table 1 to produce toner particles, externally added toner, and developer.

[0476] <Example 9-Example 10>

[0477] The same procedures as in Example 1 were carried out except that the type of the shell-forming dispersion (amorphous polyester resin particle dispersion) was changed as shown in Table 1, and toner particles, externally added toner, and developer were prepared.

[0478] <Example 11 to Example 18>

[0479] The same procedure as in Example 1 was followed, except that the concentration Wc of the first aggregated particle dispersion and the concentration Ws of the shell-forming dispersion (amorphous polyester resin particle dispersion) used in the second aggregation step were changed as shown in Table 1, to produce toner particles, an externally added toner, and a developer.

[0480] <Example 19 to Example 20>

[0481] The same procedure as in Example 1 was followed, but the amounts of the amorphous polyester resin particle dispersion (1) and the crystalline polyester resin particle dispersion (1) added were changed so that the proportion of the polyester resin particles in the total solid content in the first coagulation step was as shown in Table 1 (however, the ratio between the two amounts was the same as in Example), and toner particles, an externally added toner, and a developer were prepared.

[0482] <Example 21 to Example 24>

[0483] The same procedure as in Example 1 was carried out except that the type of the colorant particle dispersion was changed as shown in Table 1, and toner particles, externally added toner, and developer were prepared.

[0484] <Example 25 to Example 28>

[0485] Toner particles, an external toner, and a developer were prepared in the same manner as in Example 1 except that 50 parts of any of the vinyl resin particle dispersions (1) to (4) was used in the first aggregation step.

[0486] <Example 29>

[0487] The same procedure as in Example 1 was followed, except that 50 parts of the vinyl resin particle dispersion (1) was used in the first coagulation step, and the shell-forming dispersion used in the second coagulation step was changed to a shell-forming dispersion obtained by mixing 100 parts of the amorphous polyester resin particle dispersion (1) and 20 parts of the release agent particle dispersion (1), and adjusting the temperature Ts and concentration Ws as shown in Table 1, to produce toner particles, an externally added toner, and a developer.

[0488] Comparative Examples 1 and 2

[0489] The same procedure as in Example 1 was carried out except that the temperature Tc of the first aggregated particle dispersion used in the second aggregation step was changed as shown in Table 1 to produce toner particles, externally added toner, and developer.

[0490] Comparative Examples 3 and 4

[0491] In the same manner as in Example 1, except that the temperature Ts of the shell-forming dispersion (amorphous polyester resin particle dispersion) used in the second aggregation step was changed as shown in Table 1, to prepare toner particles, externally added toner, and developer.

[0492] Comparative Examples 5 and 6

[0493] The same procedure as in Example 1 was carried out except that the stirring power per unit volume (P-P0) in the second aggregation step was changed as shown in Table 1 to produce toner particles, externally added toner, and developer.

[0494] Performance Evaluation

[0495] [Particle Size Distribution of Toner Particles]

[0496] The particle size distribution of the toner particles was measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) to determine the volume average particle size and the number ratio of particles with a particle size of 2 μm or less. The number ratio of particles with a particle size of 2 μm or less was classified as follows. The results are shown in Table 1.

[0497] A: Less than 5%

[0498] B: More than 5% and less than 8%

[0499] C: More than 8% and less than 10%

[0500] D: More than 10%

[0501] [Charge amount of developer]

[0502] The developer was left overnight at 20°C and 50% relative humidity to adjust the temperature and humidity. Under the same conditions, 7.5 g of the developer was placed in a Turbula mixer and stirred. The charge (μC / g) of the developer after stirring for 10 seconds was measured using a blow-off charge meter. The difference from the developer's target charge of -43 μC / g was classified as follows. The results are shown in Table 1.

[0503] A: ±3μC / g or less

[0504] A-: More than ±3μC / g and less than ±5μC / g

[0505] B: More than ±5μC / g and less than ±7μC / g

[0506] C: More than ±7μC / g and less than ±10μC / g

[0507] D: more than ±10μC / g

[0508] The “ΔSP value” in Table 1 represents the difference between the solubility parameter of the vinyl resin used in the first coagulation step and the solubility parameter of the amorphous polyester resin used in the second coagulation step.

[0509]

[0510] The method for producing the electrostatic latent image developing toner of the present invention includes the following aspects. (1)

[0512] A method for producing a toner for developing an electrostatic latent image, comprising:

[0513] a first aggregating step of aggregating the polyester resin particles in a dispersion containing the polyester resin particles to form first aggregated particles;

[0514] a second aggregation step of mixing a dispersion containing the first aggregated particles with a dispersion containing amorphous polyester resin particles, and causing the amorphous polyester resin particles to adhere to surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles; and

[0515] a fusion step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles to form toner particles;

[0516] The second coagulation step satisfies the following formulas (1), (2) and (3):

[0517] Formula (1): 35≤Tc≤(Tgs-5),

[0518] Formula (2): 10≤Ts≤Tc,

[0519] Formula (3): 0.6≤(P-P0)≤3.0,

[0520] Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles.

[0521] Tc is the temperature (°C) of the dispersion containing the first aggregated particles at the start of mixing,

[0522] Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing,

[0523] P is the stirring power per unit volume (kW / m 3 ),

[0524] P0 is the no-load stirring power per unit volume (kW / m 3 ). (2)

[0526] The method for producing a toner for developing an electrostatic latent image according to (1), wherein:

[0527] The acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less. (3)

[0529] The method for producing a toner for developing an electrostatic latent image according to (1) or (2), wherein:

[0530] The second aggregation step further satisfies the following equations (4) and (5):

[0531] Formula (4): 10≤Wc≤20,

[0532] Formula (5): 5≤(Ws-Wc)≤20,

[0533] Wc is the solid content concentration (mass %) of the dispersion containing the first aggregated particles at the start of mixing,

[0534] Ws is the solid content concentration (mass %) of the dispersion containing the amorphous polyester resin particles at the start of mixing. (4)

[0536] The method for producing a toner for developing an electrostatic latent image according to any one of (1) to (3), wherein:

[0537] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion containing amorphous polyester resin particles and crystalline polyester resin particles.

[0538] The total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45% by mass or more of the total solid content of the dispersion containing the polyester resin particles. (5)

[0540] The method for producing a toner for developing an electrostatic latent image according to any one of (1) to (4), wherein:

[0541] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing colorant particles.

[0542] The zeta potential of the colorant particle dispersion used to prepare the dispersion is -40 mV or more and -15 mV or less, measured with the solid content concentration, hydrogen ion concentration, and temperature of the colorant particle dispersion adjusted to 10% by mass, pH 6, and 25°C. (6)

[0544] The method for producing a toner for developing an electrostatic latent image according to any one of (1) to (5), wherein:

[0545] In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl resin particles.

[0546] The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 the following. (7)

[0548] The method for producing a toner for developing an electrostatic latent image according to any one of (1) to (6), wherein:

[0549] In the second aggregation step, the dispersion containing the amorphous polyester resin particles further contains release agent particles. (8)

[0551] The method for producing a toner for developing an electrostatic latent image according to any one of (1) to (7), wherein:

[0552] The first coagulation step, the second coagulation step, and the combining step are performed in a stirring tank equipped with a stirring member and a heating and cooling member.

[0553] According to (1), (7) or (8), a method for producing a toner for electrostatic latent image development is provided, which is easier to achieve a target charge amount than when at least one of the equations (1), (2) and (3) is not satisfied.

[0554] According to (2), a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is less than 8 mgKOH / g or exceeds 16 mgKOH / g.

[0555] According to (3), a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when at least one of the equations (4) and (5) is not satisfied.

[0556] According to (4), a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when the total amount of amorphous polyester resin particles and crystalline polyester resin particles is less than 45% by mass of the total solid content of the dispersion in the first aggregation step.

[0557] According to (5), a method for producing a toner for developing an electrostatic latent image is provided, which is more likely to achieve a target charge amount than when the zeta potential of the colorant particle dispersion is less than -40 mV or exceeds -15 mV.

[0558] According to (6), a method is provided in which the difference between the solubility parameter of the vinyl resin and the solubility parameter of the amorphous polyester resin exceeds 1.0 (cal / cm 3 ) 0.5 In the case of the above, it is easy to realize the method for producing a toner for developing an electrostatic latent image having a target charge amount.

[0559] The above-described embodiments of the present invention are provided for the purpose of illustration and explanation. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed embodiments. It is obvious that various modifications and variations are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily explain the principles of the present invention and its application. Thus, other technical personnel in this field can understand the present invention through various modifications optimized for specific uses of the assumed various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

Claims

1. A method for producing a toner for developing an electrostatic latent image, comprising: a first aggregating step of aggregating the polyester resin particles in a dispersion containing the polyester resin particles to form first aggregated particles; a second aggregation step of mixing a dispersion containing the first aggregated particles with a dispersion containing amorphous polyester resin particles, and allowing the amorphous polyester resin particles to adhere to surfaces of the first aggregated particles while stirring the mixed dispersion to form second aggregated particles; and a fusion step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles to form toner particles; The second agglomeration step satisfies the following formulas (1), (2) and (3): Formula (1): 35≤Tc≤(Tgs-5), Formula (2): 10≤Ts≤Tc, Formula (3): 0.6≤(P-P0)≤3.0, Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles. Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing, Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing, P is the stirring power per unit volume (kW / m 3 ), P0 is the no-load stirring power per unit volume (kW / m 3 ).

2. The method for producing a toner for developing an electrostatic latent image according to claim 1, wherein: The acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less.

3. The method for producing a toner for developing an electrostatic latent image according to claim 1 or 2, wherein: The second agglomeration step further satisfies the following equations (4) and (5): Formula (4): 10≤Wc≤20, Formula (5): 5≤(Ws-Wc)≤20, Wc is the solid content concentration (mass %) of the dispersion containing the first aggregated particles at the start of mixing, Ws is the solid content concentration (mass %) of the dispersion containing the amorphous polyester resin particles at the start of mixing.

4. The method for producing a toner for developing an electrostatic latent image according to any one of claims 1 to 3, wherein: In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion containing amorphous polyester resin particles and crystalline polyester resin particles. The total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45% by mass or more of the total solid content of the dispersion containing the polyester resin particles.

5. The method for producing a toner for developing an electrostatic latent image according to any one of claims 1 to 4, wherein: In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing colorant particles. The zeta potential of the colorant particle dispersion used to prepare the dispersion is -40 mV or more and -15 mV or less, wherein the solid content concentration, hydrogen ion concentration and temperature of the colorant particle dispersion are adjusted to 10 mass %, pH 6 and 25° C. for measurement.

6. The method for producing a toner for developing an electrostatic latent image according to any one of claims 1 to 5, wherein: In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl resin particles. The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 the following.

7. The method for producing a toner for developing an electrostatic latent image according to any one of claims 1 to 6, wherein: In the second aggregation step, the dispersion containing the amorphous polyester resin particles further contains release agent particles.

8. The method for producing a toner for developing an electrostatic latent image according to any one of claims 1 to 7, wherein: The first aggregating step, the second aggregating step, and the combining step are performed in a stirring tank provided with a stirring member and a heating and cooling member.